Pilot database for management of drone (UAV) image data with basic functionality developed. - CGIAR Platform for Big Data in Agriculture (2019)
The database has been tested with IRRI drone / UAV data and the moment and functionalities are being developed and others fine tuned, before upscaling to other data sources and functionalities and release.